Intelligence on Threats—Municipal Management of Maritime Warnings in 15th-Century Catalonia - Victòria A. Burguera i Puigserver (Histories, 2025)
Since the early 14th century, the Mediterranean coasts of the Crown of Aragon had mechanisms in place to alert populations of incoming threats from the sea. In addition to maritime surveillance systems strategically positioned at elevated vantage points, any information reaching the coast that posed a threat to the safety of the population or trade was swiftly relayed along the shoreline, ensuring that coastal communities could prepare and defend themselves. This information, preserved in the correspondence of coastal city authorities, serves today as a primary source not only for reconstructing maritime threats in the late Middle Ages but also for assessing the role of urban leaders in managing defence. This article explores both aspects. By analysing maritime alerts either received in the city of Barcelona or disseminated from it during the first half of the 15th century, this study examines the main threats to the Catalan coastline while emphasizing the central role of cities in managing the alert system.